Recurrent immune thrombocytopenic purpura with excellent prognosis - Biyani, Garima; Azad, Syed Md; Guha, Souvik; Kapoor, Rohit; De, Hriday (International Journal of Research in Medical Sciences, 2017)
Immune thrombocytopenic purpura (ITP) is an autoimmune disorder characterized by increase in destruction of circulatory platelets and is the most common cause of acquired thrombocytopenia in childhood. ITP can be classified based on duration of thrombocytopenia as acute and chronic form. Recurrent ITP is defined as recurrence of symptoms, after at least three months of remission sustained without any treatment. It is a rare entity and seen in just 5% of all ITP cases. Further, its treatment is often cumbersome and warrants use of non-conventional drugs and splenectomy. Reported here is a case of ITP in a 10-year-old girl, who presented with three recurrences and all episodes were successfully treated with either oral Prednisolone or resolved spontaneously.